Circulation in Investment and Financing from the Perspective Islamic Economics - Adri; Prayoga, Ferdi; Izmuddin, Iiz (ICIEFS Proceeding, 2024)
Production, consumption, and distribution are interconnected economic activities, where circulation acts as the primary mechanism to channel production output to consumers. The strategy of circulation in investment and financing within the Islamic economic perspective focuses on equitable distribution through Sharia-compliant financial instruments such as mudharabah and musyarakah. These instruments enable individuals and institutions to collaborate in mutually beneficial investments, with proportional sharing of risks and profits. The circulation process within the Islamic economic system aims to establish a fair and sustainable system that evenly distributes wealth across all levels of society. This research is a literature review conducted using a qualitative descriptive method, with data gathered through literature review and documentation techniques. The data were analyzed inductively, including data reduction, presentation, and conclusion drawing. The findings suggest that by adopting Sharia-based financial instruments like mudharabah and musyarakah, along with the active role of the state in wealth distribution, the Islamic economic system strives to create an inclusive economic environment. Wealth is not concentrated among a few individuals but is distributed for the welfare of the community. This approach not only strengthens the economy but also ensures that economic benefits reach all of humanit